2000
DOI: 10.1155/np.2000.167
|View full text |Cite
|
Sign up to set email alerts
|

Age‐Related Decrease in the Schaffer Collateral‐Evoked EPSP in Awake, Freely, Behaving Rats

Abstract: Synaptic response size in the CA1 region of the hippocampus in aged rats is reduced for a given stimulus intensity, compared with that elicited in young rats. Consistent with the in vitro findings of reduced Schaffer collateral-evoked CA1 EPSPs in old rats, the population currents evoked to iontophoretically applied AMPA are also smaller relative to the presynaptic fiber potential amplitude. On the other hand, the size of the presynaptic fiber potential and amplitude of unitary intra-cellularly recorded EPSP r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
27
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 59 publications
5
27
0
Order By: Relevance
“…This reduction in NonTg mice at 8 months is most likely due to a normal age related decline of synaptic AMPAR activity, possibly related to reduced postsynaptic AMPAR activity (Barnes, Rao, and Orr, 2000; Kumar and Foster, 2007). In the 8 month old 3xTg-AD mice, this age related decline in synaptic transmission may be exaggerated due to Aβ-induced AMPAR trafficking (Hsieh, Boehm, Sato, Iwatsubo, Tomita, Sisodia, and Malinow, 2006) or changes in calcium homeostasis (Chakroborty, Kim, Schneider, Jacobson, Molgo, and Stutzmann, 2012).…”
Section: Discussionmentioning
confidence: 96%
“…This reduction in NonTg mice at 8 months is most likely due to a normal age related decline of synaptic AMPAR activity, possibly related to reduced postsynaptic AMPAR activity (Barnes, Rao, and Orr, 2000; Kumar and Foster, 2007). In the 8 month old 3xTg-AD mice, this age related decline in synaptic transmission may be exaggerated due to Aβ-induced AMPAR trafficking (Hsieh, Boehm, Sato, Iwatsubo, Tomita, Sisodia, and Malinow, 2006) or changes in calcium homeostasis (Chakroborty, Kim, Schneider, Jacobson, Molgo, and Stutzmann, 2012).…”
Section: Discussionmentioning
confidence: 96%
“…For instance, we found that the network activity generated by the OB can be reduced by the application of 30 nM Aβ in slices taken from 3-week-old animals (Figure 3), whereas it was necessary to apply 100 nM Aβ to induce a similar reduction in network activity of hippocampal slices taken from 2-week-old animals [52]. Aging has been associated with loss of synaptic contacts [83,84], silencing of synapses [83-85], or a decrease of postsynaptic responsiveness [83,84,86,87] and synaptic dynamics [68, for review see 87], which is reflected in deficits in the generation of certain spontaneous oscillatory activities [52,88]. It remains to be determined which of these phenomena is responsible for the age dependency of Aβ-induced OB network dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Aging is associated with specific impairments of hippocampal function, which is reflected in learning and memory deficit [31,48]. These deficits could be associated with the loss of synaptic contacts [49], silencing of synapses [32,50] or decrease of postsynaptic responsiveness [51] (for review see [52]). This is reflected in deficits in the generation of long term plasticity [31,52,53] as well as alterations in the generation of certain spontaneous oscillatory activities [33].…”
Section: Discussionmentioning
confidence: 99%
“…Possibly by affecting cognitive-related processes such as long term plasticity [13][14][15][16][17][18], neuronal network oscillations [11,19,20] or neuronal codification [21]. Accordingly with this line of evidence, we have recently shown that acute application of high nanomolar concentrations of mostly monomeric forms of A [25][26][27][28][29][30][31][32][33][34][35] affects hippocampal network functioning from single cell to network level, both in vitro and in vivo [11]. However, those high concentrations have been observed rarely in the brain of AD patients [22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation